Pulsed dye laser repurposed: Treatment of refractory molluscum contagiosum in renal transplant patient. Issue 2 (26th December 2018) - Fisher, Chris; McLawhorn, Justin M.; Adotama, Prince; Stasko, Thomas; Collins, Lindsey; Levin, Jarad
Abstract: We present a case of a 15‐year‐old girl with an allogenic renal transplant secondary to chronic glomerulonephritis of unknown etiology who presented with treatment refractory molluscum contagiosum of the lower extremities and perineum. Treatment of mollusca with pulsed dye laser resulted in a clinically significant and sustained response. To our knowledge, this is the first report of a successful treatment of molluscum contagiosum with pulsed dye laser in the setting of a renal transplant.